Activation of pluripotency genes in human fibroblast cells by a novel mRNA based approach. - Jordan R Plews; JianLiang Li; Mark Jones; Harry D Moore; Chris Mason; Peter W Andrews; Jie Na (PLoS ONE)
Background Several methods have been used to induce somatic cells to re-enter the pluripotent state. Viral transduction of reprogramming genes yields higher efficiency but involves random insertions of viral sequences into the human genome. Although induced pluripotent stem (iPS) cells can be obtained with the removable PiggyBac transposon system or an episomal system, both approaches still use DNA constructs so that resulting cell lines need to be thoroughly analyzed to confirm they are free of harmful genetic modification. Thus a method to change cell fate without using DNA will be very useful in regenerative medicine. Methodology/principal findings In this study, we synthesized mRNAs encoding OCT4, SOX2, cMYC, KLF4 and SV40 large T (LT) and electroporated them into human fibroblast cells. Upon transfection, fibroblasts expressed these factors at levels comparable to, or higher than those in human embryonic stem (ES) cells. Ectopically expressed OCT4 localized to the cell nucleus within 4 hours after mRNA introduction. Transfecting fibroblasts with a mixture of mRNAs encoding all five factors significantly increased the expression of endogenous OCT4, NANOG, DNMT3β, REX1 and SALL4. When such transfected fibroblasts were also exposed to several small molecules (valproic acid, BIX01294 and 5'-aza-2'-deoxycytidine) and cultured in human embryonic stem cell (ES) medium they formed small aggregates positive for alkaline phosphatase activity and OCT4 protein within 30 days. Conclusion/significance Our results demonstrate that mRNA transfection can be a useful approach to precisely control the protein expression level and short-term expression of reprogramming factors is sufficient to activate pluripotency genes in differentiated cells.